The Effect of Product Quality, Price and Promotion on Purchasing Decisions of Oppo Cellphones at Planet 99 Celuler Unaaha Store - Fitria Fitria; Adnan Chalik (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to study and analyze empirically the effect of product quality (X1), price (X2), and promotion (X3) on purchasing decisions (Y) at the Planet 99 Celuler Unaaha store, with a total sample of 30 0 people. The results of this study indicate that product quality, price, and promotion have a positive and significant effect on purchasing decisions for the Oppo cellphone at the Planet 99 Celuler Unaaha store. Product quality partially has a positive and significant effect on purchasing decisions for Oppo cellphones at the Planet 99 Cellular Unaaha store. Price has a positive and significant effect on purchasing decisions for Oppo cellphones at the Planet 99 Celuler Unaaha store. Promotion partially has a positive and significant effect on purchasing decisions for Oppo cellphones at the Planet 99 Celuler Unaaha store, data is processed using SPSS version 26.